Способ переработки гидроксидного кека, полученного при щелочном вскрытии монацитового концентрата - Егоров Н. Б. Николай Борисович; Дьяченко А. Н. Александр Николаевич; Акимов Д. В. Дмитрий Васильевич; Киселёв А. Д. Александр Дмитриевич; Обмуч К. В. Кирилл Васильевич; Литовкин С. В. Сергей Валерьевич; Ворошилов Ф. А. Федор Анатольевич; Кондрашин М. Э. Максим Эдуардович
опубл. 15.12.17